Evaluasi Komponen Proksimat Rumput Laut Sebagai Bahan Dasar Komponen Kosmetik Dan Nutraseutikal Berbasis Alami - Putnarubun, Cenny; Resulva, Indah; Hanoatubun, Marthinus I. H. (Universitas Negeri Gorontalo, 2025)
Seaweed is one of the marine biological resources rich in bioactive compounds and nutritional components, with great potential for use in the cosmetics and nutraceutical industries. This study aims to evaluate the main proximate components lipid, moisture, and ash content of several locally common seaweed species in Indonesia, particularly in the Kei Islands. The samples included Gracilaria sp, Padina australis, and Sargassum sp. Analyses were conducted using standard AOAC methods. Results showed variation among species, with moisture content ranging from 16.3–65.6%, lipid from 2.2–11.9%, and ash from 16.7–47.6%. The high ash content indicates strong mineralization potential for supplement products, while the low lipid content supports the stability of water-based cosmetic formulations. This study supports the utilization of seaweed as a natural active ingredient in the development of sustainable health and beauty products.